Branding the Revolution: Havana Club Advertising and the Fight for Cuban Authenticity. (July 2019) - Chávez, Christopher A.; Valencia, Ricardo J.
Focusing on Havana Club as a case study, we examine how an authentic Cuba has been discursively constructed by agents embedded within different political ideologies. Our research centers on advertising produced in 2015–2016, when two competing rum marketers were laying claim to the Havana Club brand: Havana Club International, an enterprise of the Cuban state, and Bacardi, a global corporation. Previous research has found that the tensions between capitalist and socialist ideologies can be bridged within a single advertisement by assigning political symbols new meanings. Drawing from both critical political economy and critical studies, we move beyond a semiotic approach and examine the professional mechanisms by which advertising practitioners encode brands with political meaning. Based on our review of internal and external documents, we found that both the Havana Club International and the Bacardi campaigns are claiming authenticity to advance similar specific economic goals while asserting competing political worldviews.